PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 016 SIMPANG POROS KECAMATAN RIMBA MELINTANG - Mulyanti, Sri Mulyanti Sri; Antosa, Zariul Antosa Zariul; Daud, Damanhuri Daud Damanhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The study design was a classroom action research (CAR). research was conducted in two cycles of four meetings and two replications of material daily. background of the problem in this study is the low student learning outcomes fourth grade intersections shaft 016 countries with an average value of 69.5% of 20 students reached the KKM beelom as many as 13 people (65%). KKM while reaching only 7 people (70%). formulation of the problem in this research